An Ayurveda Case Study on GTCS w.s.r to Apasmara Roga (AYUSHDHARA, 2024)
The word ‘Epilepsy’ is derived from Greek meaning- ‘to seize upon’. The disease Apasmara is diagnosed based upon shrewd observation of the symptoms, with the main presenting feature of this disease as “Apaya (loss) of Smriti (memory)” i.e., ‘loss of memory/ consciousness’. Apasmara occurs due to an aberration of not only the physical bio-entities Vata, Pitta and Kapha dosha but also of the psychological (Manasika) attributes like Sattva (harmonious), Rajah (passion/activity), and Tamah (inertia/ignorance). It is presented with transient appearance of unconsciousness (Tamah Pravesha) with abhorrent activities like froth from mouth, abnormal postures of the body (Vibhatsa Cheshta, referring to the involuntary movements during the seizures) and psychological symptoms like perversion of memory and cognition (Smriti-buddhi Samplava). Here the case was pre diagnosed with GTCS (generalised toni-clonic seizures) having symptoms such as decreased memory, epileptic attack 3 months ago which impersonates with Vataja Apasmara. So, in this case study an effort is made to correct the cause and the epileptic attacks with other associated symptoms by giving oral medications having predominantly Vata Shamak properties as well as Shodhana Chikitsa (Nasya).